(untitled) (Historia, 2021)
With their Volumes 37 and 39 (Second Series), the Van Riebeeck Society for the Publication of Southern African Historical Documents (VRS Hereafter) are not only continuing their tradition of producing high quality source publications, they are also breaking new ground - and hopefully setting a new trend. For a long time now this society’s publications have proven the value of approaching the collection, selection and presentation of source material as a collaborative effort between two or more scholars who could either supplement one another’s different skills, or focus their similar capabilities on one and the same subject, thus multiplying the veracity of the outcome. The VRS’ patronage has long since also included the translation of documents into English, the unofficial lingua franca in Southern African historical writing. What is new about these latest two books, Words of Batswana and Isaac Williams Wauchope, is that they are the result of collaborative work in multilanguage publishing : in these books documentation of historical and literary value written a century ago in two African languages (Setswana and isiXhosa respectively) were rescued, in the words of VRS Chairperson Howard Phillips, "from the crumbling pages of long-forgotten newspapers" (Wauchope, p xiv). Each transcription from the newspapers is accompanied with a complete translation into English. True to VRS style, the collections are contextualised with comprehensive and insightful introductions and annotations.